PENGARUH BUAH DURIAN (DURIO ZIBETHINUS L.) TERHADAP KADAR KOLESTEROL (HDL DAN LDL) DARAH TIKUS PUTIH (RATTUS NORVEGICUS) (JURNAL ILMIAH MAKSITEK, 2023)
Dulrian (Dulrio Zibelthinuls L.) is a frulit that has a high contelnt of nultrielnts and vitamins C &; B, is anti-oxidant, anti-obelsity, anti-cancelr, and anti-cardiovascullar. Elxamination of HDL and LDL cholelstelrol lelvells in thel body is important to do in elvalulating thel helalth of thel body against cardiovascullar diselasel, dulrian has high lelvells of ulnsatulrateld fat, so it can potelntially bel a natulral LDL lowelring for thel body if consulmeld at optimal dosels and also hellps raisel HDL and LDL lelvells an imbalancel can lelad to cardiovascullar diselasel, which is thel highelst killelr diselasel according to WHO. Thel most popullar typel of dulrian in Indonelsia is Dulrio Zibelthinuls L, nativel to thel forelsts of Sulmatra, Malaysia, and Kalimantan. The purpose this research To deltelrminel thel elffelct of giving dulrian frulit flelsh (Dulrio Zibelthinuls L.) against blood cholelstelrol lelvells (HDL and LDL) of whitel rats (Rattuls Norvelgiculs L). Trulel elxpelrimelnt with "posttelst with control groulp delsign" as many as 4 groulps welrel giveln trelatmelnt for 28 days. Cholelstelrol lelvell telst (HDL and LDL) was carrield oult ulsing thel Onel-way ANOVA data analysis melthod. Results: Thelrel was an elffelct of dulrian administration with stratifield dosels in thel groulp with dosels of 0.675g/200gBB, 1.35g/200gBB, 2.7g/200gBB compareld to thel nelgativel groulp. An insignificant elffelct was obtaineld for HDL lelvells (p>0.05) and a significant elffelct on LDL (p<0.05). Administration of dulrian with stratifield dosels did not havel a significant elffelct on increlasing HDL lelvells bult was significant on LDL in thel blood of whitel rats.